Cryogenic Exfoliation of Non‐layered Magnesium into Two‐Dimensional Crystals. (21st May 2019) - Zhang, Chen; Xu, Yingfeng; Lu, Ping; Wei, Chenyang; Zhu, Chenxi; Yao, Heliang; Xu, Fangfang; Shi, Jianlin
Abstract: Physical exfoliation of layered precursors is one of the most prevailing techniques to prepare two‐dimensional (2D) crystals, which, however, is considered to be intrinsically inapplicable to non‐layered bulks. Now, plane cleavage differentiation is identified in metallic magnesium at cryogenic temperature (CT), and a cryogenic exfoliation strategy of non‐layered magnesium into 2D crystals is developed. The cleavage anisotropy of the Mg lattice in response to the external mechanical stress originates from the CT‐induced specific inactivation of basal slip, which results in the basal cleavage perpendicular to c axis. The exfoliated novel 2D Mg crystals exhibit remarkable localized surface plasmon resonances, holding great promise for the applications in harvesting and converting solar energy. Beyond creating a new member for the burgeoning 2D family, this study may provide a useful tool for the physical exfoliations of various non‐layered materials. Abstract : Guten Rutsch : Basierend auf der Identifizierung der kryogenen, temperaturinduzierten spezifischen Inaktivierung von basalem Verrutschen in einem metallischen Mg‐Gerüst, die in einer Spaltungsanisotropie als Reaktion auf die externe mechanische Spannung resultiert, konnte nicht geschichtetes Mg mit richtungslosen metallischen Bindungen physikalisch zu 2D‐Kristallen bei kryogener Temperatur (CT) exfoliert werden.